PENGARUH KETERLIBATAN DEWAN KOMISARIS TERHADAP KINERJA PERUSAHAAN - Yadhi George Makarios Sagala; Paulus Th Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2019)
The aim of this research is to examine the effect of board of commissioner involvement on firm performance. The examined factors of this research are managerial ownership, board meetings frequency, board independence, and board size as independence variables, while firm performance is measured by earning per share (EPS) as dependent variable. Firm size, current ratio, auditor big 4 vs non-big 4, and firm age are also used as control variables.This research uses secondary data such as financial statements and annual reports of manufacturing companies listed on the Indonesia Stock Exchange within the period 2015-2017. Based on the purposive sampling method, there are 72 companies that met the sampling criteria. The data were analyzed using multiple linear regression. The result of this research shows that board meetings frequency has a positive significant effect on firm’s performance. Meanwhile, managerial ownership, board independence, and board size have no significant effect on firm performance.